Indoor Air Quality: Sampling Methodologies - Hess-Kosa, Kathleen (CRC Press, 2009)
Indoor Air Quality: Sampling Methodologies provides environmental professionals and industrial hygienists with the latest information available in "indoor air quality sampling." In most instances, there are no established government protocols. In this book, the author presents prominent contributions and discusses the practical concerns that determine which sampling approach is best for a given situation.